Exploring pathways of regional technological development in China through patent analysis - Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
[Introduction] Over the course of the past two decades, China has evolved from a nation focused on production to a technologically dynamic one with the ambition to catch up with the world's leading economies by 2050 (Schwaag Serger and Breidne 2007; State Council (of the People's Republic of China) 2006). Since 2011, it has become the nation with largest annual patent output in the world (Reuters 2011). At the same time, however, China also remains a huge country in which substantive disparities continue to prevail (Kroll 2010; Liefner and Wei 2013). For a long time, talking about new technological trends and growing capacity in China was almost identical to talking about new devel-opments in Beijing, Guangdong, and Greater Shanghai. At the same time, this meant talking about two separate research systems, a public and an industrial one that were distinct, not only in terms of their legacy and internal logics (Motohashi 2008), but also in terms of their geographical representation (Kroll and Frietsch 2014; Kroll and Schiller 2010). As a result, meaningful knowledge transfer between these two systems only occurred in a limited number of 'islands of innovation', where regionally unique systems of co-operation had developed over the years (Kroll and Liefner 2008; Kroll and Schiller 2010). [...]
urn:nbn:de:0011-n-3476753
Keywords: 330